Recalled Parenting As Predictor of Regulatory Focus of Young Adults - Brković, Irma (Array, 2009)
Regulatory focus is the concept introduced by Higgins (1997). Regulatory-focus theory proposes that nurturance- and security-related regulations differ in regulatory focus. He distinguishes promotion focus (involved in nurturance regulation) and prevention focus (involved in security regulation). Promotion focus is a concern with advancement, growth and accomplishment. Prevention focus, on the other hand, is a concern with protection safety and responsibility. The aim of this research is to examine the relation between parenting of both parents and promotive and preventive focus of their children in order to explore one of the basic assumptions that regulatory foci are adopted during socialization, within caretaker-child interaction. Regulatory Focus Questionnaire consists of two (prevention and promotion) subscales. URP-29 is 29-item questionnaire that measures seven dimensions of parental behavior (Acceptance, Autonomy, Psychological Control, Monitoring, Permissiveness, Positive discipline and Negative discipline). Participants were 137 1st and 2nd year students from Zagreb University (87% female, mean age 20 yrs). They completed all questionnaires twice, 3 weeks apart. They were instructed to report on how they remember their parents’ behaved during their primary school. For regulatory focus items they were instructed to focus on present. Test-retest reliabilities were high for assessing recalled parenting (0.72– 0.92) and moderate for regulatory focus (0.49 for Promotion and 0.75 for Prevention focus). These results are in accordance with the theoretical notion that momentary situations can induce either a promotion or prevention focus. The results show that parenting accounts for low to moderate, but significant, proportion of variance of regulatory foci. Prevention focus is better explained by parenting than Promotion focus, with Negative discipline and Acceptance of mothers being significant predictors. Fathers’ Negative discipline and Acceptance were also significant predictors, together with Fathers Psychological control. Promotive regulatory focus was not significantly predicted by parenting of any parent.